Optimization of the angle of attack of delta-winglet vortex generators in a plate-fin-and-tube heat exchanger - Lenouedda, Abdellah; Breuer, Michael; Franz, Eberhard; Botsch, Tilman; Delgado, Antonio (International Journal of Heat and Mass Transfer, 2010)
Delta-winglet vortex generators (VGs) are known to enhance the heat transfer between the energy-carrying fluid and the heat transfer surfaces in plate-fin-and-tube banks. In this study optimal angles of attack of the delta-winglets are investigated based on the Pareto optimal strategy. The optimization process combines a CFD analysis, genetic algorithms and the response surface methodology. The angle of attack of a pair a delta-winglet-type VGs mounted behind each tube is varied between β = -90° and +90°. Three circular tube rows with inline and staggered tube arrangements are investigated for Reynolds numbers from 200 to 1200 (based on the inlet height and inlet velocity). The flow structure and heat transfer behavior is analyzed in detail for certain cases and the staggered and the inline tube arrangements are compared. Finally, for each of these arrangements the optimal sets of angles of attack for different Reynolds numbers are presented. © 2010 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2010.tech.ITC.stmmec.optimi
Keywords: Genetic algorithms; Heat transfer enhancement; Pareto optimality; Response surface methodology; Vortex generators